Practice of successful extubation from mechanical ventilation in a patient with ICU-acquired weakness and related integrated traditional Chinese and western medicine nursing (1例重症监护室获得性衰弱患者成功脱机的中西医结合护理) - ZHANG Jing (张静); ZHOU Xinyi (周馨怡) (中西医结合护理)
This paper summarized the practice of successful extubation from mechanical ventilation in a patient with acquired weakness and related integrated traditional Chinese and western medicine nursing management. The patient was diagnosed with intensive care unit-acquired weakness caused by intracranial infection of viral encephalitis, and underwent tracheotomy and continuous ventilator-associated ventilation. A large amount of oral and subglottic secretions overflowed through the tracheotomy site, and the patient had frequent hiccups, which seriously affected respiratory function exercise and delayed weaning time. Based on the systematic evaluation of patient’s condition, a nursing plan of integrated traditional Chinese and western medicine interventions was conducted: timely clearing subglottic secretions, and preventing the occurrence of VAP; adopting appropriate techniques including auricular acupoint pressing, acupoint application, acupuncture and moxibustion to alleviate hiccup symptoms; strengthening rehabilitation of respiratory function exercise, psychological care and health education. The nursing plan with appropriate traditional Chinese medicine and Western medicine treatments had effectively relieving the hiccup symptoms and improve the recovery of respiratory function, and successful extubation from mechanical ventilation was achieved. (本文总结1例重症监护室获得性衰弱患者成功脱机的中西医结合护理实践经验。本例患者因病毒性脑炎颅内感染导致获得性衰弱, 行气管切开持续呼吸机辅助通气, 大量口腔及声门下分泌物经气管切开处外溢, 同时患者存在频发呃逆症状, 严重影响呼吸功能锻炼, 延迟脱机时间。护理团队完善系统评估, 制定中西医结合护理方案: 机械通气护理精准清除声门下分泌物, 预防呼吸机相关肺炎的发生; 穴位贴敷、耳穴压丸、针灸、艾灸序贯疗法缓解呃逆; 程序化呼吸肌康复; 加强心理护理和健康教育。经干预, 患者呃逆消失, 痰液黏稠度下降, 呼吸功能改善, 并顺利脱机。)